Identificação de perfis de consumo de serviços por bairros de Fortaleza - Bezerra, Gabriel Alencar (2020)
The tertiary sector, known for encompassing the activities of trade in goods and provision of services, shows significant relevance in the Brazilian economy, especially in the service sector. Examples of service providers are schools, colleges, beauty salons, petshops, health plans, gyms and workshops. In Brazil, a country of continental dimensions, it is complex to offer infrastructure in order to provide such services, whether public or private. In a less broad perspective, both this peculiarity, as well as the importance of the sector, applies to states and municipalities. From this, this dissertation aims to analyze the flow of service provision in the city of Fortaleza, in order to verify consumption profiles, taking into account the districts of the provider and borrower of these services. For this, data extracted from values of electronic service invoices - NFS of the city of Fortaleza were used from 01/01/2013 to 11/30/2019. The results show that the Meireles and Aldeota neighborhoods presented themselves as the largest borrowers in the entire period analyzed, while the center presents itself as the main service provider in the city of Fortaleza. Based on the use of the Herfindahl – Hirschman Index (IHH), a drop in the concentration of service providers is observed, a contrary movement when analyzing providers. Finally, it was found that the variables used were statistically significant, but have a low explanatory power for the model. From these results, it is hoped to provide subsidies for a possible public policy to promote the provision of certain services in places where there is a shortage.